Chikungunya virus disease outbreak in Yap State, Federated States of Micronesia. - Daniel M Pastula; W Thane Hancock; Martin Bel; Holly Biggs; Maria Marfel; Robert Lanciotti; Janeen Laven; Tai-Ho Chen; J Erin Staples; Marc Fischer; Susan L Hills (Public Library of Science (PLoS), 2017)
BACKGROUND:Chikungunya virus is a mosquito-borne alphavirus which causes an acute febrile illness associated with polyarthralgia. Beginning in August 2013, clinicians from the Yap State Department of Health in the Federated States of Micronesia (FSM) identified an unusual cluster of illness which was subsequently confirmed to be chikungunya virus disease. Chikungunya virus disease previously had not been recognized in FSM. METHODOLOGY/PRINCIPAL FINDINGS:Information from patients presenting to healthcare facilities was collected and analyzed. During August 11, 2013, to August 10, 2014, a total of 1,761 clinical cases were reported for an attack rate of 155 clinical cases per 1,000 population. Among residents of Yap Main Island, 3% were hospitalized. There were no deaths. The outbreak began on Yap Main Island and rapidly spread throughout Yap Main Island and to three neighboring islands. CONCLUSIONS/SIGNIFICANCE:Chikungunya virus can cause explosive outbreaks with substantial morbidity. Given the increasing globalization of chikungunya virus, strong surveillance systems and access to laboratory testing are essential to detect outbreaks.